Intertextual Study of the Short Story Menuju Pulang by Indrian Koto and the Short Story Orion by A. Masyitta - Euis Shalihah; Maizar Karim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
In this research, researchers used descriptive qualitative methods. In this research, the approach used is an intertextual approach, where this intertextual approach compares two texts that have a connection or relationship and this intertextual approach is also used to find hypograms and transformations in short stories Menuju rumah and the short story Orion. These two short stories have almost the same theme elements, namely about returning home and longing after not returning home for a long time and home is not just a place to live, but home is the first place where we smile and cry.